Genetic diversity of black soldier flies in Vietnam based on DNA COI sequence - THI NHIEN NGUYEN; THI BINH NGUYEN TRAN; HOANG NAM TRAN (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Nguyen TN, Tran TBN, Tran HN. 2023. Genetic diversity of black soldier flies in Vietnam based on DNA COI sequence. Biodiversitas 24: 6727-6732. The Black Soldier Fly (BSF), Hermetia illucens (Linnaeus, 1758), is found in temperate and tropical regions of the world. In recent years, BSF has been cultivated as fodder in some areas of Vietnam. The genetic diversity of BSF in Vietnam has not yet been assessed. This study aimed to investigate the nucleotide diversity in COI sequences of BSF in Vietnam. We examined the COI nucleotide sequences of 22 BSFs using flies or larval tissue samples for DNA extraction and subsequent sequencing. Our analysis showed that the nucleotide composition of BSF consisted of 25.36% A, 36.04% T, 21.25% C, and 17.35% G, with a significant prevalence of A+T nucleotides of 61.40% compared to 38.60% for G+C nucleotides. Among 22 individual BSFs samples collected from ten provinces and cities, spanning seven agro-ecological regions in Vietnam, we identified 9 different haplotypes, which were distributed in five clades but mainly clustered in two main clades: E and F. Clade E, prominently represented by branch E, showed a higher abundance in Asia, while Clade F has been identified in Europe, Uganda, South Korea, Oceania and North America. Our results highlight the relatively high genetic diversity of the Vietnamese BSF population. In addition, the COI nucleotide sequences of these Vietnamese BSF samples were similar to those of Asian and Australian countries, showing significant similarities to the Palearctic and Oriental regions. These results provide valuable insights to inform BSF breeding and development in Vietnam.